PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR WILAYAH DIREKTORAT JENDRAL PAJAK KALIMANTAN BARAT - Tampubolon B1110905, Hardyanto Pandapotan (Jurnal Manajemen Update, 2015)
This research was titled " Effects of Leadership Style and Work Discipline Against The Performance of Employees on the Territory of the Directorate General of Tax Office in West Borneo ". The purpose of this research is to examine and analyze the influence of leadership styles and discipline work against the performance of employees on the territory of Directorate General Tax Office of West Borneo. This research uses research causality and survey methods. In this sudy, there is a population of as many as 84 people and all of them were used as samples by means of a cencus. Data collection techniques using questionnaires, interviews, observation and studies of the literature. Data analysis methods used include validity test, reliability test with Alpha Cronbach, classic assumption test and multiple linear regression analysis to test and prove the hypotheses of the study. Data analysis in this study uses the help of SPSS 17. Conclusion of this research is the leadership style, work discipline and employee performance in the Regional Offices the Tax Directorate General of West Borneo belong to either. The test result by using SPSS 17 shows that leadership style and work discipline affect employee performance significantly to either simultaneously or partially. In addition, a more dominant variables affect the performance of the employee was work discipline. Keywords: Leadership styles, discipline work, employee performance.